UJI FISIK FORMULASI TABLET FLOATING TEOFILIN DENGAN MATRIK HPMC - Dewi Rashati, Siti Mursidatur Rohmah (AKADEMI FARMASI JEMBER, 2016)
The purpose of this study was to determine the physical properties of theophylline floating tablet formulation with HPMC as matrix. Floating tablets of theophylline is manufactured by direct compression. Composition per tablet formulation consisting of theophylline 270 mg, HPMC, avicel, magnesium stearate, and sodium bicarbonate. The results of data showed average of tablet weight uniformity 501mg, tablet hardness 6,99 kg, tablet friability 0,593%, disintegration time of tablets 738 seconds, floating lag time (FLT) 584,3 seconds and floating duration time (FDT) more than 8 hours. Floating tablet formulation of theophylline resulted in a good physical test.Keyword: floating, theophylline, HPMC, tablet